PENEGAKAN HUKUM TERHADAP PERMASALAHAN LINGKUNGAN HIDUP UNTUK MEWUJUDKAN PEMBANGUNAN BERKELANJUTAN - Nisa, Anika Ni'matun (Jurnal Bina Mulia Hukum, 2020)
Pollution and environmental damage is a serious problem. Therefore there is a need for law enforcement efforts that have an important role as agents of stability. Law Enforcement can be used as a benchmark for overcoming environmental problems based on Undang-Undang Nomor 32 Tahun 2009 concerning Environmental Management and Protection. This law can be used as the main key so that law enforcement can be carried out properly to realize sustainable development. This study aims to analyze law enforcement on environmental issues to realize sustainable development. The method used in writing this article is the normative juridical approach. Sources of data obtained are using various journal and book reviews related to law enforcement, environmental issues, and sustainable development. The results of the study can be concluded that law enforcement on environmental issues to realize sustainable development is very necessary for the future. Law enforcement as a bridge must be able to provide a deterrent effect on perpetrators of pollution and environmental damage for the sake of creating sustainable development for a better life.